PENGARUH MOTIVASI , DISIPLIN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KEBUDAYAAN DAN PARIWISATA KOTA SEMARANG - Dara Rizky Arwinda, 13.05.51.0170 (Students Journal of Economic and Management, 2017)
This study analyzed on the influence of motivation, discipline dan work environtment on employee performance. Object of this research at Depertment of Culture and Turism City of Semarang. Subject of this study use all population and number of population is 103 respondents. Data collection method using a questionnaire by distributing a list of question to the respondent in order to obtain information. The research objectives was formulated to determine the effect of motivation, discipline, and work environtment on employee performance at Department of Culture and Turism City of Semarang. The data used primary data, analysed using regression analysis. The result showed that the motivation, discipline, and work environtment had a positive significant effect on employee performance at Depertment of Culture and Turism City of Semarang. From these result can be concluded that high motivation, high working discipline, and a good work environtment will improve employee performance at Depertment of Culture and Turism City of Semarang . Keywords : Motivation, Discipline, Work Environtement and Employee Performance